2019
DOI: 10.1186/s43057-019-0007-7
|View full text |Cite|
|
Sign up to set email alerts
|

Outcome of MC3 ring annuloplasty for moderate and severe functional tricuspid regurgitation associated with rheumatic mitral valve disease

Abstract: Background: To evaluate early and midterm outcomes of tricuspid ring annuloplasty using three-dimensional (3D) MC3 ring for treatment of functional tricuspid regurgitation (FTR) during mitral valve replacement for rheumatic valve disease. Results: This prospective study included 105 patients who underwent repair for ≥ moderate tricuspid regurgitation (TR) during mitral valve replacement for rheumatic valve disease. Between January 2016 and December 2018, a group of 23 patients who underwent ring annuloplasty w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…
In a recently published article by Al-Elwany et al [1] in The Cardiothoracic Surgeon, the authors reported that the rate of recurrence of tricuspid regurgitation was 4.3% after MC3 ring annuloplasty and 23.1% after DeVega repair. Therefore, we have a correction for a statement in the abstract and section of methods within the text telling that (The rate of TR recurrence (≥ 2+ TR) was significantly higher after MC3 ring annuloplasty).
…”
mentioning
confidence: 99%
“…
In a recently published article by Al-Elwany et al [1] in The Cardiothoracic Surgeon, the authors reported that the rate of recurrence of tricuspid regurgitation was 4.3% after MC3 ring annuloplasty and 23.1% after DeVega repair. Therefore, we have a correction for a statement in the abstract and section of methods within the text telling that (The rate of TR recurrence (≥ 2+ TR) was significantly higher after MC3 ring annuloplasty).
…”
mentioning
confidence: 99%